Optimalisasi Penggunaan Aplikasi Whatsapp dan Google Meet Dalam Pembelajaran Masa Pandemi Covid-19 - Eliana Nur Laeli (STAI Bumi Silampari, 2021)
Learning during the pandemic covid-19 is done online. Learning media based on information technology in the form of electronic learning can be used as a solution to the learning process during the pandemic covid-19.This study aims to analyze the use of whatsaap and google meet applications as optimization of online learning during the pandemic covid-19.This research is library research because all the data is sourced from library materials, books, articles, research journals, and documents relevant to the focus of research.This research revealed that collaboration of the use of whatsapp and google meet applications can help in the learning process, the use of whatsapp group can be enabled to send material files and the use of google meet can be enabled for virtual learning process, material delivery and question and answer discussion.